The effect of online “Love and Care” self-compassion practice among Malaysian counselling students - Mei, Jin Lim; Joo, Siang Tan (Penerbit Universiti Kebangsaan Malaysia, 2023)
The purpose of this study is to investigate the effect of online self-compassion practice on selfcompassion, emotional regulation, and perceived wellbeing in counselling students. Counsellors are exposed to high risks of psychological and emotional distress, therefore self-compassion as self-care strategy is essential to be cultivated among counselling students. In this study, purposive sampling was employed to recruit participants via the internet. Thirty-two counselling students participated in a 14-day online program as an intervention of self-compassion practice. Data for self-compassion, emotional regulation and perceived wellbeing were collected before, after and 1 month follow up of the program. Data were analyzed using nonparametric Friedman test. The result shows the potential of such intervention by revealing improvements in several measures over two weeks and supported partial hypotheses. Firstly, the findings shows that the daily selfcompassion practice has a significant effect on self-compassion, specifically self-kindness, and mindfulness. Secondly, there is also significant difference on wellbeing. Lastly, supported with qualitative data in participants’ survey, the overall experience with daily self-compassion practice is all positively worded. Both quantitative and qualitative findings from our present study showed that the intervention greatly increase participants’ sense of self-kindness and perceived wellbeing throughout the 14 days. Overall, this study supports the previous studies on the effectiveness of self-compassion and further supports the wellbeing of counselling students. The implication of the study is self-compassion and wellbeing could be promoted through a short intervention program via online platform, and it may serve as a support tool to other traditional forms of intervention.